Family traditional bakery business sustainability: an analysis on its contributing success factors - Misran, Norsyahidatun Naim; Mohd Sharif, Mohd Shazali; Saad, Mazni; Ab Karim, Shahrim; Ramly, Alina Syuhaida (Human Resource Management Academic Research Society, 2021)
The waves of civilization, industrialization, technological innovations, economic growth and increasing welfare of people have undoubtedly altered or changed the traditional food culture, including the traditional food products. Some might argue that the traditional foods products are slightly over ruined by the modern foods that seem to be more attractive and trendier. Whether this connotation holds true is not known. This paper attempted to identify the factors that affect the continuation of the family traditional food business. It mainly focused on Salahuddin Bakery located in Johor Baharu that offers their family traditional bakery production. Salahuddin Bakery has been operating for more than 80 years since 1937. The ethnographic technique through observation approach was undertaken for seven days. A narrative analysis approach was applied in reporting the findings. Results revealed that five main factors led the bakery to continuously sustain itself. Premise, products, equipment, material, customer and knowledge transfer were the factors identified. Although some alterations were made in line with the modernisation, it did not involve the recipes, which were part of their family culture practice that has remained up to the fourth generation. In this sense, preserving and transferring the family food and business knowledge is one of the essential factors in determining the successful sustainability of the traditional family food business.